Non-Pharmacology Therapy For Reducing Vascular Inflammation Among Type 2 Diabetes Mellitus Patient: A Literature Review - Sirait, Healthy Seventina; Said, Faridah Mohd; Mohamad, Nur Afiqah (Holistic Nursing Plus, 2025)
Backgrund: Type 2 diabetes mellitus (T2DM) is a chronic condition marked by persistently high blood sugar levels. Chronic inflammation in blood vessels is a significant concern, leading to cardiovascular complications. Pharmacological therapies have side effects, and non-pharmacological therapies are gaining interest. This study aimed to identify effective non-pharmacological therapies to reduce vascular inflammation in T2DM patients and understand their mechanisms. Methods: A narrative literature review was conducted, searching articles published between 2015 and 2025 in PubMed, ScienceDirect, and Google Scholar. Inclusion criteria were studies on T2DM patients, written in English or Indonesian, and meeting quality thresholds. Results: The search identified 1152 articles. After a multi-step screening process following the PRISMA framework, a final set of articles was selected for analysis. The review identified various non-pharmacological therapies, including physical therapy interventions (FIR therapy, acupuncture, hydrotherapy), exercise training (HIIT with RT, MCT with RT, yoga), and lifestyle/nutritional interventions (diabetes education, MNT, yoga). These therapies improved blood circulation, reduced inflammation markers, enhanced metabolic function, and improved glycemic control. Discussion: Non-pharmacological therapies offer promising strategies for managing T2DM. FIR therapy